Control of inverted pendulum:| comparison of various strategies for swing up and balancing - Er, Fatih. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2005., 2005)
In this thesis, two different control schemes are designed for swinging up and three different schemes for balancing of an inverted pendulum, a non-linear electro-mechanical system with open loop unstablity. The controllers which are implemented for experimental purpose are a heuristic control technique using fuzzy logic and an energy control technique for swinging up. In order to balance the pendulum in the upright equilibrium, state feedback control, LQR control which is an optimal control technique and well known traditional control technique PID control are implemented. The control objective is swinging up the pendulum from its initial downward equilibrium to the upward and then balance at this state while it is tracking of desired trajectory. Three different combinations of proposed control schemes are chosen and their performances are compared with each other. Having compared all combinations, it is observed that every controller has advantages and merits for different cases.
Keywords: Control systems.; Fuzzy logic.; Nonlinear control theory.; H2 control.